2024
DOI: 10.1038/s41598-024-52389-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between visual impairment and mental disorders

Alireza Hashemi,
Hassan Hashemi,
Alireza Jamali
et al.

Abstract: To determine the association between visual impairment (VI) and some mental disorders using the general health questionnaire (GHQ) in individuals aged 60 years and above in Tehran, Iran. The present population-based cross-sectional study was conducted on people aged 60 and older in Tehran, Iran using multi-stage cluster sampling. After selecting the samples, examinations including visual acuity measurement, refraction, and slit-lamp biomicroscopy were performed for all participants. The GHQ was used to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Visual impairment also affects daily functioning. Hashemi et al, (2024) found that depression, anxiety, and physical problems are more common in individuals with visual impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Visual impairment also affects daily functioning. Hashemi et al, (2024) found that depression, anxiety, and physical problems are more common in individuals with visual impairment.…”
Section: Introductionmentioning
confidence: 99%